Preliminary image evaluation performance of radiographers in one New Zealand District: a 6‐month prospective study - Kim Lewis; Sibusiso Mdletshe; Andrea Doubleday; Tracey Pieterse (Journal of Medical Radiation Sciences)
Abstract Introduction Preliminary image evaluation (PIE) is a system where radiographers alert emergency department referrers to the presence or absence of abnormalities on acute extremity X‐ray examinations. PIE and similar systems have been utilised in the United Kingdom (UK) and Australia due to a shortage of radiologists to provide a timely report. As New Zealand (NZ) faces a similar shortage, PIE should be considered to address the negative impact this has on patients. The aim of this study was to determine the effect of regular feedback and education on radiographers' performance when detecting and describing acute abnormalities on extremity X‐ray examinations in ED. Methods A prospective longitudinal study design was utilised for this study. The sensitivity, specificity, accuracy, and accuracy of PIEs performed by seven radiographers at a public provincial district in NZ were assessed over a 6‐month period, with the participants provided monthly results along with regular e‐mailed feedback on common errors. Results The mean for sensitivity, specificity, and accuracy calculated with a 95% confidence interval over the 6‐month period were 92.8% (89.9, 95.8), 94.9 (93.1, 96.8), and 94.2 (91.9, 96.5), respectively. When the month‐to‐month results were analysed, the results demonstrated an improvement in participants' sensitivity, specificity, and accuracy over the 6‐month period. Conclusion The results of this study demonstrated that radiographers who participated in the study can perform PIE to a high standard that is comparable with the findings from international studies and demonstrated an improvement over 6 months. Therefore, PIE may be useful in NZ to aid ED clinicians in their clinical decisions when a radiology report is unavailable.